'China in Africa': From Under-researched to Under-theorised?. (January 2015) - A'Zami, Darius
The literature on China–Africa relations is a rapidly developing field. However, whilst it is a much richer body of work now than it was a few years ago, it has been somewhat resistant to compelling theorisation. This claim is demonstrated via discussion of three recent contributions to this literature. The discussion develops a claim that a helpful problématique might be found by framing China–Africa relations as relations between 'unequal equals', a particular benefit of which is that it emphasises that China–Africa relations are, inter alia specifically international relations. Whilst rigorous theoretical work has already been done, the emphasis has been societal. In this sense, the unequal equals formulation amounts to a call for greater dialogue between social and internationally oriented disciplines to resolve the under-theorisation that afflicts the study of China–Africa relations.